The elicitation of steady‐state visual evoked potentials during sleep. (18th January 2017) - Norton, James J. S.; Umunna, Stephen; Bretl, Timothy
Abstract: This study confirmed the hypothesis that it is possible to elicit SSVEPs through closed eyelids during NREM sleep. To test this hypothesis, SSVEP amplitudes were measured in eight subjects across two conditions of stimulation (stimulation on and stimulation off) and three brain states (waking, light sleep, and deep sleep). Results showed a significant interaction between stimulation and brain state. In particular, EEG activity at the frequency of stimulation was higher during both light sleep and deep sleep in the stimulation on condition than in the stimulation off condition. The fact that it is possible to elicit SSVEPs during sleep may provide a new way to study how SSVEPs are generated in the brain—one that might help resolve open questions such as identifying the SSVEP activation sequence or deciding if SSVEPs derive from evoked or oscillatory neural processes.